Optical Probe Ion and Carrier Dynamics at the CH3NH3PbI3 Interface with Electron and Hole Transport Materials. Issue 22 (13th October 2016) - Wen, Xiaoming; Huang, Shujuan; Chen, Sheng; Deng, Xiaofan; Huang, Fuzhi; Cheng, Yi‐Bing; Green, Martin; Ho‐Baillie, Anita
Abstract : Ion migration and accumulation in perovskite and interface have recently attracted considerable research interest because it is closely related to carrier extraction and hence to the performance of perovskite solar cells. Here using specific optical probe techniques and perovskite, the authors investigate the effect of light illumination (soaking) at the CH3 NH3 PbI3 /spiro‐OMeTAD and CH3 NH3 PbI3 /Phenyl‐C61‐butyric‐acid‐methyl ester interfaces, focusing on the dynamics of mobile ions and photoexcited carriers. Time dependent photoluminescence (PL) intensity, electron–hole recombination and optical microscopy images are used to monitor the illumination effects at the interface as a function of light illumination time and intensity. Under continuous illumination, the PL intensity exhibits dynamic quenching in the timescale of seconds to minutes. The authors attribute this PL quenching to the accumulation of mobile ions at the interface during light soaking. Only negative ions cause such PL quenching and the rate at which PL intensity decreases depends on the illumination intensity. The authors found that the accumulated ions also impede the extraction of photogenerated holes from the perovskite layer into spiro‐OMeTAD, which increases electron–hole recombination. This investigation provides novel insight into the ion migration mechanism by light soaking and therefore its impact on the operation of a perovskite solar cell. Abstract : Light soaking effect at the CH3 NH3 PbI3 /spiro‐OMeTAD and CH3 NH3 PbI3 /PCBM interfaces is investigated using time dependent photoluminescence (PL) intensity, time‐resolved PL, and optical microscopy images, focusing on the dynamics of mobile ions and photoexcited carriers. Negative ion accumulation is found to result in PL quenching at the interface of perovskite and spiro, which impedes the extraction of photogenerated holes.